Adoption of Green River Project Fish Farming Technologies by Farmers in Niger Delta Region of Nigeria - O I Ogbonna; E A Onwubuya; O M Akinnagbe (Journal of Agricultural Extension, 2014)
The study assessed adoption of improved fish farming technologies by fish farmers as well as socioeconomic characteristics of respondents, level of adoption of GRP fish farming technologies and constraints to adoption of the technologies. The hypothesis of the study was that socioeconomic conditions of farmers do not significantly influence adoption of GRP technologies. Multistage sampling technique was used to select 120 respondents from two states in Niger Delta. Descriptive statistics, regression analysis and factor analysis were used to analyze data. Results showed that majority (76.7% and 77.5%) of the fish farmers were male and married respectively. Mean age of the respondents was 50 years and majority were literates. Majority of the respondents adopted fish farm management technologies (79%), feeding techniques (79%), fish culture management techniques (77%) and water quantity and quality management techniques (88%). Constraints to adoption of the technologies included technology- related constraints such as existence of technologies better than GRP technologies (with loading of 0.536) and input- related constraints such as: late arrival of GRP input (0.760). Result of the hypothesis was that some socioeconomic characteristics of farmers (age and years spent in school) affected adoption. It was recommended that there should be involvement of youths in the project, provision of sufficient inputs to farmers at the right time and measures to increase collaboration between GRP and other agencies that disseminate improved fish farming technologies in the area.